Directory of animal production projects in the Caribbean - Lauckner, F B (CARDI St AugustineTT, 1987)
Includes all projects reported to CARDI as initiated or completed at 1977. For each project the following information is listed (where available): name and address of project leader(s); institution(s) executing project; project title; objectives; crops and/or livestock under investigation; main aspect of research; starting date (actual or estimated); summary of findings. Lists projects alphabetically by country, institute and leader.